2015
DOI: 10.1128/jvi.03197-14
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Interaction of Stress Granules, DDX3X, and IKK-α Mediates Multiple Functions in Hepatitis C Virus Infection

Abstract: The ubiquitous ATP-dependent RNA helicase DDX3X is involved in many cellular functions, including innate immunity, and is a pivotal host factor for hepatitis C virus (HCV) infection. Recently, we showed that DDX3X specifically recognizes the HCV 3= untranslated region (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 60 publications
(87 reference statements)
6
79
0
Order By: Relevance
“…In agreement with previous studies, some DDX3X could also be detected in the nucleus (Fig. 5, insets), consistent with its shuttling across the nuclear envelopes (24,25). Upon infection, DDX3X levels were once again unaffected in HeLa and Vero cells but reduced in 143B cells, as reported above.…”
Section: Resultssupporting
confidence: 79%
“…In agreement with previous studies, some DDX3X could also be detected in the nucleus (Fig. 5, insets), consistent with its shuttling across the nuclear envelopes (24,25). Upon infection, DDX3X levels were once again unaffected in HeLa and Vero cells but reduced in 143B cells, as reported above.…”
Section: Resultssupporting
confidence: 79%
“…DDX3X also enhances MAVS function and this effect is blocked by HCV core protein (Oshiumi et al, 2010). Interestingly, DDX3X bound to the 3´UTR of HCV relocates to stress granules and lipid droplets and activates IKKα, which exerts an NF-κΒ-independent function and translocates to the nucleus to induce the expression of lipogenic genes (Li et al, 2013a;Pene et al, 2015). Thus, sensing HCV genome in the infected cell by DDX3X initiates transcription of lipogenic genes essential for viral assembly.…”
Section: Role Of Hcv In the Modulation Of The Interferon Responsementioning
confidence: 88%
“…For example, the SG protein DDX3 may be redistributed in several ways in order to participate in replication, assembly or even secretion of HCV. For instance, DDX3‐containing SGs may be used to activate lipid droplet formation and studies have demonstrated that DDX3 is recruited to participate in replication complexes (along with G3BP1) . Like P‐body components, DDX3 suppression has been shown to reduce HCV RNA in vitro, in the same manner as G3BP1, ATX2, HuR1, PABP1 and USP10 .…”
Section: How Hcv Plays With P‐bodies and Sgs Without Getting Burnedmentioning
confidence: 99%
“…For instance, DDX3‐containing SGs may be used to activate lipid droplet formation and studies have demonstrated that DDX3 is recruited to participate in replication complexes (along with G3BP1) . Like P‐body components, DDX3 suppression has been shown to reduce HCV RNA in vitro, in the same manner as G3BP1, ATX2, HuR1, PABP1 and USP10 . In addition, sequestering DDX3 may also serve an additional mechanism for counteracting cell immunity since DDX3 is part of the interferon (IFN) response …”
Section: How Hcv Plays With P‐bodies and Sgs Without Getting Burnedmentioning
confidence: 99%